Connecting research and practice to enhance the evolutionary potential of species under climate change. Issue 2 (3rd January 2023) - Thompson, Laura M.; Thurman, Lindsey L.; Cook, Carly N.; Beever, Erik A.; Sgrò, Carla M.; Battles, Andrew; Botero, Carlos A.; Gross, John E.; Hall, Kimberly R.; Hendry, Andrew P.; Hoffmann, Ary A.; Hoving, Christopher; et al.
Abstract: Resource managers have rarely accounted for evolutionary dynamics in the design or implementation of climate change adaptation strategies. We brought the research and management communities together to identify challenges and opportunities for applying evidence from evolutionary science to support on‐the‐ground actions intended to enhance species' evolutionary potential. We amalgamated input from natural‐resource practitioners and interdisciplinary scientists to identify information needs, current knowledge that can fill those needs, and future avenues for research. Three focal areas that can guide engagement include: (1) recognizing when to act, (2) understanding the feasibility of assessing evolutionary potential, and (3) identifying best management practices. Although researchers commonly propose using molecular methods to estimate genetic diversity and gene flow as key indicators of evolutionary potential, we offer guidance on several additional attributes (and their proxies) that may also guide decision‐making, particularly in the absence of genetic data. Finally, we outline existing decision‐making frameworks that can help managers compare alternative strategies for supporting evolutionary potential, with the goal of increasing the effective use of evolutionary information, particularly for species of conservation concern. We caution, however, that arguing over nuance can generate confusion; instead, dedicating increased focus on a decision‐relevant evidence base may better lend itself to climate adaptation actions.